Teachers' perception of self-employment efforts among tertaiary institutions graduates in Cross River state of Nigeria (2007)
Students' poor performance in secondary school economics has been attributed to the introduction of mathematical economics. In view of this prevailing problem, this study investigated teachers' perception of the quantitative aspects of senior secondary school economics syllabus. The influence of some teacher factors (gender, qualification, years of teaching experience and area of specialisation) on the perception of the quantitative aspects of economics were examined. The study is a non-experimental research. The population consisted of economics teachers in the south- west region of Nigeria. The subjects of the study comprised 172 economics teachers randomly selected from 70 sampled schools in Oyo and Ondo state. A Teacher' Perception of Quantitative aspect of economics questionnaire (TPOQAEQ) was used to collect data. The reliability of the instrument using Cronbach Alpha formula yielded a coefficient of 0.73. The data collected were subjected to both descriptive and inferential statistics which included t-test and ANOVA. The study revealed that teachers seems to have fiarly high positive perception of the quantitative aspects of economic syllabus. Also, the study showed a significant difference in teachers' perception of quantitative aspects of economics in terms of qualification and years of teaching experience while gender and area of specialisation were not significant. Suggestions were made for improving teaching and learning of the quantitative aspects of economics at the secondary school level in the region.